Tumor Immune Microenvironment and Immunotherapy in Brain Metastasis From Non-Small Cell Lung Cancer - Wang, Yuchang; Chen, Rui; Wa, Yue; Ding, Shikuan; Yang, Yijian; Liao, Junbo; Tong, Lei; Xiao, Gelei (Frontiers in Immunology, 2022)
Brain metastasis (BM), a devastating complication of advanced malignancy, has a high incidence in non-small cell lung cancer (NSCLC). As novel systemic treatment drugs and improved, more sensitive imaging investigations are performed, more patients will be diagnosed with BM. However, the main treatment methods face a high risk of complications at present. Therefore, based on immunotherapy of tumor immune microenvironment has been proposed. The development of NSCLC and its BM is closely related to the tumor microenvironment, the surrounding microenvironment where tumor cells live. In the event of BM, the metastatic tumor microenvironment in BM is composed of extracellular matrix, tissue-resident cells that change with tumor colonization and blood-derived immune cells. Immune-related cells and chemicals in the NSCLC brain metastasis microenvironment are targeted by BM immunotherapy, with immune checkpoint inhibition therapy being the most important. Blocking cancer immunosuppression by targeting immune checkpoints provides a suitable strategy for immunotherapy in patients with advanced cancers. In the past few years, several therapeutic advances in immunotherapy have changed the outlook for the treatment of BM from NSCLC. According to emerging evidence, immunotherapy plays an essential role in treating BM, with a more significant safety profile than others. This article discusses recent advances in the biology of BM from NSCLC, reviews novel mechanisms in diverse tumor metastatic stages, and emphasizes the role of the tumor immune microenvironment in metastasis. In addition, clinical advances in immunotherapy for this disease are mentioned.